Intrapancreatic Accessory Spleen: Investigative Dilemmas and Role of EUS-Guided FNA for Diagnostic Confirmation - Krishna, Somashekar G; Heif, Muhannad M; Sharma, Shree G; Pandey, Tarun; Rego, Rayburn F (JOP. Journal of the Pancreas, 2011)
<!--[if gte mso 9]> 1024x768 <![endif]--><!--[if gte mso 9]> Normal 0 14 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Context We submit a case of intrapancreatic accessory spleen. Case report A 33-year-old patient with history of dyspepsia underwent imaging studies suggestive of a neuroendocrine tumor. After referral to our institute, endoscopic ultrasound guided fine needle aspiration (EUS-FNA) confirmed diagnosis as intrapancreatic accessory spleen. Discussion An accessory spleen may develop from estranged mesenchymal cells due to fusion failure of the splenic anlage. The prevalence of an accessory spleen is 10-30% with 80% of them present at the splenic hilum and 17% in the pancreatic tail. Intrapancreatic accessory spleen is commonly misdiagnosed as a pancreatic tumor. Since, the differential diagnosis includes pancreatic neuroendocrine tumors, additional investigation with EUS-FNA should be considered when radiological diagnosis is not definitive. Conclusion For diagnosis of intrapancreatic accessory spleen, radiographic imaging is useful, but lacks specificity without tissue diagnosis. Diagnosis can be safely and reliably established with EUS-FNA, leading to a benign prognosis and avoidance of unnecessary surgical intervention.